Conservative versus Interventional Management of Ingested Straight Pins in Adolescent Females: A Retrospective Case Series Illustrating Guideline-Based Decision-Making - Purnamasari, Primadita; Sigit Adi Prasetyo; Rudiyuwono Raharjo (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: The ingestion of sharp foreign bodies (FBs) in adolescents presents a critical management dilemma, balancing conservative observation against the risk of gastrointestinal perforation. In certain cultural contexts, the accidental ingestion of straight pins used for hijabs creates a unique patient cohort. This study aims to illustrate the practical, guideline-based application of divergent management strategies in these specific clinical scenarios. Methods: We conducted a retrospective case series of five female adolescents, aged 13 to 15 years, managed at a single tertiary center for accidental straight pin ingestion. Data on clinical presentation, radiological findings, management strategy (conservative versus endoscopic), and outcomes were extracted and analyzed. Management decisions were dictated by established international guidelines. Results: Three asymptomatic patients (60%) with pins located distal to the duodenum were managed conservatively and experienced spontaneous passage within 2-4 days. Two patients (40%) required therapeutic endoscopy. One underwent emergent removal for a proximally located pin causing respiratory symptoms. The other, despite being asymptomatic, underwent urgent intervention due to the development of a radiological "sentinel loop" and rising inflammatory markers, which revealed an impacted duodenal pin. No complications occurred in any patient. Conclusion: This series demonstrates that while active surveillance is a safe strategy for asymptomatic patients with distally located sharp FBs, clinical silence does not preclude impending complications. Subtle radiological findings, such as a sentinel loop, are crucial indicators that must prompt timely endoscopic intervention to prevent morbidity. The educational value lies in highlighting these critical decision-making triggers.